Multibridge VO2‐Based Resistive Switching Devices in a Two‐Terminal Configuration - Xing Gao; Thijs J. Roskamp; Timm Swoboda; Carlos M. M. Rosário; Sander Smink; Miguel Muñoz Rojo; Hans Hilgenkamp (Advanced Electronic Materials, 2023)
Abstract Vanadium dioxide exhibits a hysteretic insulator‐to‐metal transition (IMT) near room temperature, forming the foundation for various forms of resistive switching devices. Usually, these are realized in the form of two‐terminal bridge‐like structures. The authors show here that by incorporating multiple, parallel VO2 bridges in a single two‐terminal device, a wider range of possible characteristics can be obtained, including a manifold of addressable resistance states. Different device configurations are studied, in which the number of bridges, the bridge dimensions, and the interbridge distances are varied. The switching characteristics of the multibridge devices are influenced by the thermal cross‐talk between the bridges. Scanning thermal microscopy (SThM) is used to image the current distributions at various voltage/current bias conditions. This work presents a route to realize devices exhibiting highly nonlinear, multistate current–voltage characteristics, with potential applications in, e.g., tunable electronic components and novel, neuromorphic information processing circuitry.